Dissection of a sensorimotor circuit underlying pathogen aversion in C. elegans - Adam Filipowicz; Jonathan Lalsiamthara; Alejandro Aballay (BMC Biology, 2022)
Abstract Background Altering animal behavior to reduce pathogen exposure is a key line of defense against pathogen attack. In Caenorhabditis elegans, alterations in intestinal physiology caused by pathogen colonization and sensation of microbial metabolites may lead to activation of pathogen aversive behaviors ranging from aversive reflexes to learned avoidance. However, the neural circuitry between chemosensory neurons that sense pathogenic bacterial cues and the motor neurons responsible for avoidance-associated locomotion remains unknown. Results Using C. elegans, we found that backward locomotion was a component of learned pathogen avoidance, as animals pre-exposed to Pseudomonas aeruginosa or Enterococcus faecalis showed reflexive aversion to drops of the bacteria driven by chemosensory neurons, including the olfactory AWB neurons. This response also involved intestinal distention and, for E. faecalis, required expression of TRPM channels in the intestine and excretory system. Additionally, we uncovered a circuit composed of olfactory neurons, interneurons, and motor neurons that controls the backward locomotion crucial for learned reflexive aversion to pathogenic bacteria, learned avoidance, and the repulsive odor 2-nonanone. Conclusions Using whole-brain simulation and functional assays, we uncovered a novel sensorimotor circuit governing learned reflexive aversion. The discovery of a complete sensorimotor circuit for reflexive aversion demonstrates the utility of using the C. elegans connectome and computational modeling in uncovering new neuronal regulators of behavior.